Multiomics and bioinformatics identify differentially expressed effectors in the brain of Toxoplasma gondii infected masked palm civet - Yuan, Hao; Jiang, Tiantian; Zhang, Wei-Dong; Yang, Zipeng; Luo, Shengjun; Wang, Xiaohu; Zhu, Xiaojing; Qi, Shuting; Mahmmod, Yasser S.; Zhang, Xiu-Xiang; Yuan, Zi-Guo (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The masked palm civet (Paguma larvata) serves as a reservoir in transmitting pathogens, such as Toxoplasma gondii, to humans. However, the pathogenesis of T. gondii infection in masked palm civets has not been explored. We studied the molecular changes in the brain tissue of masked palm civets chronically infected with T. gondii ME49. Methods The differentially expressed proteins in the brain tissue were investigated using iTRAQ and bioinformatics. Results A total of 268 differential proteins were identified, of which 111 were upregulated and 157 were downregulated. KEGG analysis identified pathways including PI3K-Akt signaling pathway, proteoglycans in cancer, carbon metabolism, T-cell receptor signaling pathway. Combing transcriptomic and proteomics data, we identified 24 genes that were differentially expressed on both mRNA and protein levels. The top four upregulated proteins were REEP3, REEP4, TEP1, and EEPD1, which was confirmed by western blot and immunohistochemistry. KEGG analysis of these 24 genes identified signaling cascades that were associated with small cell lung cancer, breast cancer, Toll-like receptor signaling pathway, Wnt signaling pathways among others. To understand the mechanism of the observed alteration, we conducted immune infiltration analysis using TIMER databases which identified immune cells that are associated with the upregulation of these proteins. Protein network analysis identified 44 proteins that were in close relation to all four proteins. These proteins were significantly enriched in immunoregulation and cancer pathways including PI3K-Akt signaling pathway, Notch signaling pathway, chemokine signaling pathway, cell cycle, breast cancer, and prostate cancer. Bioinformatics utilizing two cancer databases (TCGA and GEPIA) revealed that the four genes were upregulated in many cancer types including glioblastoma (GBM). In addition, higher expression of REEP3 and EEPD1 was associated with better prognosis, while higher expression of REEP4 and TEP1 was associated with poor prognosis in GBM patients. Discussion We identified the differentially expressed genes in the brain of T. gondii infected masked palm civets. These genes were associated with various cellular signaling pathways including those that are immune- and cancer-related.